Effects of isobutyrate supplementation in pre- and post-weaned dairy calves diet on growth performance, rumen development, blood metabolites and hormone secretion. (8th November 2016) - Wang, C.; Liu, Q.; Zhang, Y. L.; Pei, C. X.; Zhang, S. L.; Guo, G.; Huo, W. J.; Yang, W. Z.; Wang, H.
Abstract : Isobutyrate supplements could improve rumen development by increasing ruminal fermentation products, especially butyrate, and then promote the growth performance of calves. The objective of this study was to evaluate the effects of isobutyrate supplementation on growth performance, rumen development, blood metabolites and hormone secretion in pre- and post-weaned dairy calves. In total, 56 Chinese Holstein male calves with 30 days of age and 72.9±1.43 kg of BW, blocked by days of age and BW, were assigned to four groups in a randomized block design. The treatments were as follows: control, low-isobutyrate, moderate-isobutyrate and high-isobutyrate with 0, 0.03, 0.06 and 0.09 g isobutyrate/kg BW per calf per day, respectively. Supplemental isobutyrate was hand-mixed into milk of pre-weaned calves and the concentrate portion of post-weaned calves. The study consisted of 10 days of an adaptation period and a 50-day sampling period. Calves were weaned at 60 days of age. Seven calves were chosen from each treatment at random and slaughtered at 45 and 90 days of age. BW, dry matter (DM) intake and stomach weight were measured, samples of ruminal tissues and blood were determined. For pre- and post-weaned calves, DM intake and average daily gain increased linearly ( P <0.05), but feed conversion ratio decreased linearly ( P <0.05) with increasing isobutyrate supplementation. Total stomach weight and the ratio of rumen weight to total stomach weight tended to increase ( P =0.073) for pre-weaned calves and increased linearly ( P =0.021) for post-weaned calves, whereas the ratio of abomasum weight to total stomach weight was not affected for pre-weaned calves and decreased linearly ( P <0.05) for post-weaned calves with increasing isobutyrate supplementation. Both length and width of rumen papillae tended to increase linearly for pre-weaned calves, but increased linearly ( P <0.05) for post-weaned calves with increasing isobutyrate supplementation. The relative expression of messenger RNA for growth hormone (GH) receptor and 3-hydroxy-3-methylglutaryl-CoA synthase 1 in rumen mucosa increased linearly ( P <0.05) for pre- and post-weaned calves with increasing isobutyrate supplementation. Blood concentrations of glucose, acetoacetate, β -hydroxybutyrate, GH and IGF-1 increased linearly ( P <0.05) for pre- and post-weaned calves, whereas blood concentration of insulin decreased linearly with increasing isobutyrate supplementation. The present results indicated that isobutyrate promoted growth of calves by improving rumen development and its ketogenesis in a dose-dependent manner.